Part A Development of a Fluorescence Resonance Energy Transfer assay or high throughput screening for catalysts in the desymmetrization of meso substrates Part B Application of hydrazide based catalyst in Friedel-Crafts alkylation - Chin, Ami Jun-Yee (University of Ottawa (Canada), 2006)
Highthroughput methods have been increasingly applied to catalyst screening, however, efforts to use these for enantioselective measures are still lacking. We propose to apply Fluorescence Resonance Energy Transfer (FRET) as a highthroughput screening method to fulfill such a purpose. This concept is applied to the desymmetrization of meso substrates. The meso compound will be equipped with a recognition element for catalyst binding, two different fluorescence donor molecules to distinguish between the chiral centres and also a fluorescence acceptor molecule to suppress fluorescence. Upon catalytic hydrolysis, the fluorescence acceptor molecules will be discharged into solution and thus can be detected by use of a spectrophotometer. As each donor molecule has a characteristic fluorescence emission wavelength, measuring the respective fluorescence intensities will ultimately allow for one to rapidly determine the enantiomeric excess. Efforts towards establishing this FRET based assay are discussed herein.* *Please refer to dissertation for diagrams.
Keywords: Chemistry, Analytical.